Cooling channel design for improving quality of injection plastic product - Nghia, Pham Tuan (Tạp Chí Khoa học Trường Đại học Quốc tế Hồng Bàng, 2023)
Injection molding is the most widely used technique for making the related plastic parts for consumer electronics goods with limited lifespans, like mobile phones, which are growing more and more popular. The molten plastic beads must be injected into a mold cavity, cooled, then part-formed and ejected. Filling, packing, cooling, and ejection are the four key steps in an injection molding process. The length of the molding cycle affects how economical the procedure is. The cooling step is the most crucial of the three since it controls how quickly are produced. Otherwise, cooling systems are important for the injection molding process in terms of productivity, quality, and mold-making costs. In this paper, three conformal cooling channel designs are proposed for obtaining uniform cooling over the molded parts. The research is conducted by using CAE software (MOLDEX 3D) to simulate the injection process and compare the results of three conformal cooling channel designs with molded part cooling by moldbase. All three designs show that warpage and cycle time improve significantly, helping to decrease cost and increase productivity. In which the combination of a conformal cooling channel outside and a baffle cooling channel significantly reduces the warpage.